Balance between nitrogen use efficiency and cadmium tolerance in Brassica napus and Arabidopsis thaliana. (July 2019) - Liao, Qiong; Jian, Shao-Fen; Song, Hai-Xing; Guan, Chun-Yun; Lepo, Joe Eugene; Ismail, Abdelbagi M.; Zhang, Zhen-Hua
Highlights: Reduced V-ATPase and V-PPase activity improved nitrogen use efficiency. Reduced V-ATPase and V-PPase activity decreased Cd 2+ tolerance. Decreased NO3 − vacuolar sequestration capacity (VSC) enhanced Atclca-2 Cd 2+ VSC. Enhanced Cd 2+ VSC decreased NO3 − VSC in AtCAX4-OE . Regulating Cd 2+ and NO3 − vacuolar accumulation enhances NUE and Cd 2+ tolerance. Abstract: The transmembrane transport of NO3 − and Cd 2+ into plant cell vacuoles relies on the energy from their tonoplast proton pumps, V-ATPase and V-PPase. If the activity of these pumps is reduced, it results in less NO3 − and Cd 2+ being transported into the vacuoles, which contributes to better nitrogen use efficiency (NUE) and lower Cd 2+ tolerance in plants. The physiological mechanisms that regulate the balance between NUE and Cd 2+ tolerance remain unknown. In our study, two Brassica napus genotypes with differential NUEs, xiangyou 15 and 814, and Atclca-2 mutant and AtCAX4 over-expression line ( AtCAX4-OE ) of Arabidopsis thaliana, were used to investigate Cd 2+ stress responses. We found that the Brassica napus genotype, with higher NUE, was more sensitive to Cd 2+ stress. The AtCAX4-OE mutant, with higher Cd 2+ vacuolar sequestration capacity (VSC), limited NO3 − sequestration into root vacuoles and promoted NUE. Atclca-2 mutants, with decreased NO3 − VSC, enhanced Cd 2+ sequestration into root vacuoles and conferred greater Cd 2+ tolerance than the WT. This may be due to the competition between Cd 2+ andNO3 − in the vacuoles for the energy provided by V-ATPase and V-PPase. Regulating the balance between Cd 2+ and NO3 − vacuolar accumulation by inhibiting the activity of CLCa transporter and increasing the activity of CAX4 transporter will simultaneously enhance both the NUE and Cd 2+ tolerance of Brassica napus, essential for improving its Cd 2+ phytoremediation potential.